PENGARUH MINAT DAN REWARD TERHADAP MOTIVASI BELAJAR SISWA SMPS KRISTEN BNKP TELUKDALAM T.P 2019/2020 - Sesilianus Fau (Institut Pendidikan Tapanuli Selatan, 2021)
This research is designed by the variation of students’ learning motivation at school and at home. Interest and reward are presumed to have the most dominant influence on students’ learning motivation. This research aimed at examining the influence both of interest and reward on the learning motivation of students of SMPS Kristen BNKP Telukdalam in 2019/2020. The sample size determination of this research used Slovin formula and simple random sampling technique about 59 persons. The instrument used in this research was questionnaire. The data of the research was analyzed by multiple regression statistics using Statistical Product and Service Solutions (SPSS). The result of the research showed that the interest and reward gave significant influence on learning motivation of students of SMPS Kristen BNKP Telukdalam with 39.6 %. Suggestion: (1) Students are expected to maintain and to increase more the feeling of convenience, interest, attention, and activeness in every learning at school in order the learning interest is more maintained well and the learning motivation is also increased. Moreover, the students are also expected to make educational and positive reward that has been received as stimulus or reinforcement of their learning motivation both at school and outside of school, (2) Counseling teachers, subject teachers, and parents are expected to synergize to establish good communication and cooperation to increase students’ learning interest and to give educational and positive reward (such as praise, gift, applause, prayer, and publish) to the students when doing something good and positive, and achieving their learning successfully in order to increase their motivation to learn both at school and at home.